Combined systemic immune-inflammatory index and prognostic nutritional index predict outcomes in advanced non-small cell lung cancer patients receiving platinum-doublet chemotherapy - Fan, Ruiyun; Chen, Ying; Xu, Guopeng; Pan, Wen; Lv, Yantian; Zhang, Zhongwei (Frontiers in Oncology, 2023)
Background Systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI) could evaluate the therapeutic efficacy and prognosis in different tumors. However, no studies investigated the SII-PNI score to predict outcomes in non-small cell lung cancer (NSCLC) patients treated with platinum-doublet chemotherapy. The aim of this study was to investigate the SII-PNI score in predicting outcomes in non-small cell lung cancer (NSCLC) patients treated with platinum-doublet chemotherapy. Materials and methods Our study retrospectively analyzed clinical data from 124 patients with advanced NSCLC receiving platinum-doublet chemotherapy. The SII and PNI were calculated based on peripheral blood cell counts and serum albumin, and the optimal cut-off values were determined using receiver operating characteristic (ROC). All patients were divided into three groups according to the SII-PNI score. The association between the SII-PNI score and the clinicopathological characteristics of the patients was examined. The Kaplan-Meier and Cox regression models were used to assess progression-free survival (PFS)and overall survival (OS). Results There was no significant correlation between SII, PNI at baseline and chemotherapy response in patients with advanced NSCLC (p>0.05). However, after receiving 4 cycles of platinum-doublet chemotherapy, the SII of the SD group (p=0.0369) and PD group (p=0.0286) was significantly higher than that of the PR group. At the same time, the PNI of the SD group (p=0.0112) and the PD group (p=0.0007) was significantly lower than that of the PR group. The PFS of patients with SII-PNI scores of 0, 1, and 2 were 12.0, 7.0, and 5.0 months, and the OS of patients with SII-PNI scores of 0, 1, and 2 were 34.0, 17.0, and 10.5 months, respectively. There was statistical significance among the three groups (all p <0.001). Multivariate analyses showed that the chemotherapy response of progressive disease (PD) (HR, 3.508; 95% CI, 1.546-7.960; p=0.003) and SII-PNI score of 2 (HR, 4.732; 95% CI, 2.561-8.743; p < 0.001) were independently associated with a shorter OS. The uses of targeted drugs (HR, 0.543; 95% CI, 0.329-0.898; p=0.017) and immune checkpoint inhibitors (HR, 0.218; 95% CI, 0.081-0.584; p=0.002) were protective factors for OS in patients with NSCLC. Conclusion Compared with baseline parameters, the correlation between SII, PNI after 4 cycles of chemotherapy and the chemotherapy effect was more significant. The SII-PNI score after 4 cycles of chemotherapy is an effective prognostic biomarker for advanced NSCLC patients treated with platinum-doublet chemotherapy. Patients with a higher SII-PNI score had a worse prognosis.